Transcription factor 3 is dysregulated in megakaryocytes in myelofibrosis - Ryan J Collinson; Lynne Wilson; Darren Boey; Zi Yun Ng; Bob Mirzai; Hun S Chuah; Rebecca Howman; Carolyn S Grove; Jacques A J Malherbe; Michael F Leahy; Matthew D Linden; Kathryn A Fuller; et al. (Platelets)
Transcription factor 3 (TCF3) is a DNA transcription factor that modulates megakaryocyte development. Although abnormal TCF3 expression has been identified in a range of hematological malignancies, to date, it has not been investigated in myelofibrosis (MF). MF is a Philadelphia-negative myeloproliferative neoplasm (MPN) that can arise de novo or progress from essential thrombocythemia [ET] and polycythemia vera [PV] and where dysfunctional megakaryocytes have a role in driving the fibrotic progression. We aimed to examine whether TCF3 is dysregulated in megakaryocytes in MPN, and specifically in MF. We first assessed TCF3 protein expression in megakaryocytes using an immunohistochemical approach analyses and showed that TCF3 was reduced in MF compared with ET and PV. Further, the TCF3-negative megakaryocytes were primarily located near trabecular bone and had the typical “MF-like” morphology as described by the WHO. Genomic analysis of isolated megakaryocytes showed three mutations, all predicted to result in a loss of function, in patients with MF; none were seen in megakaryocytes isolated from ET or PV marrow samples. We then progressed to transcriptomic sequencing of platelets which showed loss of TCF3 in MF. These proteomic, genomic and transcriptomic analyses appear to indicate that TCF3 is downregulated in megakaryocytes in MF. This infers aberrations in megakaryopoiesis occur in this progressive phase of MPN. Further exploration of this pathway could provide insights into TCF3 and the evolution of fibrosis and potentially lead to new preventative therapeutic targets.